RANCANG BANGUN WEBSITE UKM PANAHAN UNIVERSITAS HASANUDDIN - Eliyah A M Sampetoding; Muhammad Al Fudhail; Aulia Adha Putri; Muchtar Adam Al-Hamid; Yulita Sirinti Pongtambing; Ruwaidah Ilyas; Esther Sanda Manapa; Rendy Luis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The development of information technology is currently growing rapidly over time, which provides many conveniences in various aspects of human life. The internet is one of the results of information technology which is an information resource that is able to reach the whole world. The website is a means to get the information we order easily and can be accessed anytime and anywhere, so it's not surprising that nowadays many companies need a website. This web-based Archery UKM application is an application that aims to make it easier for students to know various things about archery both in terms of new members. Prospective members will later fill out the registration form on the website, so that prospective members do not need to take the form directly because they can register online by filling out the form provided on the UKM Archery website easily, so there is no need to pay.